THE ROLE OF COOPERATIVE INSTITUTION AND BANKING INSTITUTION FOR BUSINESS CONTINUITY (GOING CONCERN) OF TRADITIONAL MARKET TRADER IN PUCANG SURABAYA - Nur Aina; Nurul Hasanah Uswati Dewi (The Indonesian Accounting Review, 2013)
The existence of many large modern markets around Pucang Market becomes a challenge formarket traders to be sustainable or going concern. This study aimed to determine the role of cooperativeand banking institutions for business continuity of traditional market in Surabaya PucangMarket. It uses descriptive qualitative in which focuses on issues or phenomena that exist atthe time of the research conducted or actual problems, then describe the facts about the issuesunder investigation accompanied by rational and accurate interpretation. The data was collectedthrough direct interviews and observations to the merchant market and ask the data to the Headof Pucang Market. From interviews and observations can be known that the loan is on offer aswell as the cooperative bank does not affect business continuity, because of fearing the risk of notbeing able to pay for borrowing at banks or cooperatives so that the development of the businessonly from the results of operations. The implication of this study is that cooperatives and banksshould create a program to improve going concern traditional market traders.